(untitled) - FAO (Rome, 1997)
This report presents long term scenarios describing interactions between livestock, crop production and land use and the possible consequences for the nutrients required for crop production and anumal waste. The livestock-crop interactions also play an important role in the emission of atmospheric pollutants. As an example, scenarios of the emission of ammonia ( NH3 ) and nitrous oxide ( N2O ) from animal excreta and synthetic fertilizers are present, as well as projections of the emission of methane ( CH4 ) by ruminating animals.
Keywords: natural resources